Techno-optimism and digital risks in public discourse: The paradox of digitalization in Kazakhstan - Makatova, Anara; Rezvushkina, Tatyana; Karasseva, Natalya; Kapiyat, Dinara (International Journal of Innovative Research and Scientific Studies, 2025)
This paper examines the phenomenon of techno-optimism in Kazakhstan, focusing on how it interacts with public discussions about the risks and negative effects of digitalization. The study is based on a computer-assisted content analysis of 120,751 messages from 22,909 unique authors across various online public sources, complemented by qualitative analysis of selected messages. The theoretical framework is paradox theory, which is applied to unstructured online discourse. The analysis tests and rejects the hypothesis that discourse on the negative effects of digitalization permeates the broader debate on digitalization. While concerns about risks are evident, they remain isolated from the general discourse on the pace and direction of digital transformation. A paradox of techno-optimism emerges: enthusiasm for digitalization persists alongside awareness of risks, with both discourses coexisting but not intersecting. The study demonstrates that techno-optimism in Kazakhstan is resilient, sustained even in the presence of risk awareness. This coexistence of contradictory discourses without integration reflects the dynamics of digitalization debates in rapidly transforming societies. The findings offer insights for policymakers and practitioners seeking to understand the public perception of digital transformation. They also highlight the importance of considering paradoxical dynamics in digital policy communication and public engagement strategies.